Mixed Eccrine Cutaneous Tumor with Folliculo–Sebaceous Differentiation: Case Report and Literature Review - Dimitrinka Kisova; Tihomir Dikov; Vesela Ivanova; Hristo Stoyanov; Greta Yordanova (Medicina, 2023)
Background/Introduction: Cutaneous mixed tumor is a rare benign neoplasm that exhibits a wide range of metaplastic changes and differentiation in the epithelial, myoepithelial, and stromal components, which is often confused with various other skin lesions. Case report: We present an unusual case of a 58-year-old woman with a mixed tumor of the upper lip, previously misdiagnosed as adnexal carcinoma on a preoperative biopsy. The excision biopsy shows a well-circumscribed lesion composed of various cells and structures featuring folliculo–sebaceous differentiation embedded in a prominent chondromyxoid stroma. The immunohistochemical study proves the various lineages of differentiation and classifies the neoplasm as the less common eccrine subtype of cutaneous mixed tumor. Discussion: The common embryologic origin of the folliculo–sebaceous apocrine complex leads to a great histological variety of cellular components of mixed tumors and the formation of structures that resemble established types of adnexal neoplasms, which could be a diagnostic pitfall, especially on a small incision biopsy.